Soft Tissue Lesions With High Vascular Density on Sonography in Pediatric Patients: Beyond Hemangiomas. Issue 4 (November 2020) - Zaltsberg, Gali Shapira; Spring, Shanna; Malic, Claudia; Koujok, Khaldoun; Davila, Jorge; Hurteau, Julie; Shenouda, Nazih
Infantile hemangiomas are the most frequent vascular soft tissue lumps in the pediatric population. The clinical presentation and evolution of these lesions is characteristic, while the sonographic appearance is classic but not specific. This pictorial essay illustrates the different vascular soft tissue lumps on ultrasound that may mimic infantile hemangiomas. Awareness of these mimics is crucial to avoid misdiagnosis. Clinical and sonographic discriminators for each lesion are presented.